If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + -7 = t + 25 Reorder the terms: -7 + 9t = t + 25 Reorder the terms: -7 + 9t = 25 + t Solving -7 + 9t = 25 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -7 + 9t + -1t = 25 + t + -1t Combine like terms: 9t + -1t = 8t -7 + 8t = 25 + t + -1t Combine like terms: t + -1t = 0 -7 + 8t = 25 + 0 -7 + 8t = 25 Add '7' to each side of the equation. -7 + 7 + 8t = 25 + 7 Combine like terms: -7 + 7 = 0 0 + 8t = 25 + 7 8t = 25 + 7 Combine like terms: 25 + 7 = 32 8t = 32 Divide each side by '8'. t = 4 Simplifying t = 4
| 5x-2/3 | | 4t-7=t+25 | | log(5x)=-1 | | 5(4y+3)=8 | | y/5.2=3.4=4.3 | | (8-6i)-(-7+i)= | | 3ax^2+2ax+1=0 | | 0=-1.225x^2+1.73x+1 | | 3s+20=4s | | (a-bi)((a+bi)+1)=11+3i | | -x+2x-1=0 | | 650+88m=650m | | 247*11= | | 2x-14=x+40 | | 0=-12x^2+156x | | 6[1-(5x-2)]=8(3-3x) | | 4q-34=2q | | 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 | | 8-(4n-8)=-8 | | 2(x-1)=3x-7 | | 25-2x=15 |